El periódico mural, revistas manuscritos - Terrones Esquivel, Yandelín Stefany (2019)
The learning session purpose is to obtain relevant information about the wall newspaper, magazines and manuscripts, to introduce the students of the first grade of Secondary Education of the Educational Institution "Rafael Narváez Cadenillas" through the analysis of a collage of images. In order to obtain information, the originality, flexibility and fluidity, as shown in the examples, were examined. Likewise, for communication skills, such as logical coherence between information and requirements, the examples proposed were examined too. As an analysis result, we concluded that students show high levels of flexibility, fluency and clarity to understand the wall newspaper function; that originality is low due to the tendency of imitate the worked examples; that students develop greater capacity for understanding when they know the context and dominate the communicative environment; and also that group work is more productive than individual work.